The Potential of Defatted Yellow Mealworm (Tenebrio molitor) Meal as an Alternative Protein Source for Juvenile Chinese Mitten Crab (Eriocheir sinensis) - Wenxiang Yao; Chunyan Zhang; Sai Zhang; Guoan Hua; Sitong Zhao; Huiyang Shuang; Ningyang Sun; Yijun Sun; Lumpan Poolsawat; Jianguo Wang; Quan Wang (Aquaculture Nutrition)
This study was aimed to investigate the effects of replacing dietary fish meal (FM) with defatted yellow mealworm (Tenebrio molitor) meal (DYM) on growth performance, intestinal health, serum immune, and antioxidant indexes of juvenile Chinese mitten crab (Eriocheir sinensis). Four hundred juvenile Chinese mitten crabs (4.94 ± 0.08 g) were randomly distributed into five groups in quadruplicate (20 crabs per tank), and each group was fed with diets that replaced FM with DYM at 0% (CON, containing 200 g/kg FM), 25% (DYM25), 50% (DYM50), 75% (DYM75), and 100% (DYM100) for 8 weeks, respectively. The results showed that the growth, serum immune and antioxidant indexes, digestive enzyme activities, intestinal histology, and microbiota composition of DYM25, DYM50, and DYM75 groups all reached the similar level as the CON group. While when 100% fishmeal was replaced, significantly decreased the final body weight (FBW), weight gain (WG), serum alkaline phosphatase (AKP), acid phosphatase (ACP), lysozyme (LZM), glutathione peroxidase (GSH-Px), total antioxidant capacity (T-AOC), and total superoxide dismutase (T-SOD) activities, hepatopancreas protease activity, mid-intestine folds height and number (P<0.05), significantly increased the feed conversion ratio (FCR), serum malondialdehyde (MDA) content, and the abundance of intestinal harmful bacteria Shewanella (P<0.05). Overall, these results suggest that 75% dietary FM (150 g/kg) can be effectively replaced by DYM without negative impact on the growth performance, intestinal health, serum immune, and antioxidant indexes of juvenile E. sinensis.